Social Consciousness, Metaphysical Contents and Aesthetics in Select Anglophone African Factions (2014)
Anglophone African factions, which are narratives containing a blend of African real-life socio-political events and fictive accounts, and which sometimes connect writers‘ metaphysical reference with their social consciousness and aesthetics, is central to literary expression in Africa. Yet, studies in African literature have focused on these philo-literary features only in fiction, neglecting their engagement in factions, thus barring a balance in African literary scholarship. This study, therefore, investigated the connection between social consciousness, metaphysical contents and aesthetics in African factions, with a view to establishing their role in the writers‘ creative vision. The research employed George Herbert Mead‘s theory of interactionism, the principle of mutual social relation, in investigating the writers‘ pursuit of social goals, aided by their metaphysical leaning in the selected texts. Four Anglophone African factions were purposively selected, for regional and gender balance. These included Nomad by Anyaan Hirsi Ali(East Africa), A Dream Fulfilled by Thandi Lujabe-Rankoe(Southern Africa), You must Set Forth at Dawn by Wole Soyinka(West Africa) and A Daughter of Isis by Nawal el Saadawi(North Africa). The texts were subjected to literary analysis. Four indexes of social consciousness were observed across the factions sampled: the Somali war, racial segregation in South Africa, military brutality in Nigeria and gender imbalance in Egypt. These were respectively fictionalised within the ambits of idealisation, infallibility, fairness and equality. The hostile socio-political environment in Africa informed the writers‘ references to metaphysical phenomena in advancing their goals. This manifested in atheist spirituality in Nomad, where Ali battles the spiritual aspect of the blood line and links human creative inspiration to atheist consciousness. It was also noted in references to African spirits such as Ngai in A Dream Fulfilled where Lujabe-Rankoe pursues folk liberation from apartheid and sees her reunion with folks after exile as divine and, so, makes supplications to Southern African spirits. It reflected in eulogy for deities such as Oro and Orunmila in You must Set Forth at Dawn where Soyinka describes the Oro festival he witnessed as ‗blissful‘ and this invigorated him on exile journey through Benin Republic, and seeks reunion with Pierre ‗under the canopy of ‗Orunmila‘ in the afterlife. This animist consciousness also reflects in A Daughter of Isis where Saadawi pursues the rights of women in Egypt through Isis. When in danger while advancing her social cause, Saadawi claims the spirits are with her and she is ‗no longer alone‘. References were also made to the Supreme Being by all the writers for inspiration. The writers express their social and metaphysical temper in the factions through aesthetic resources, such as goal-oriented code mixing, creative sentence inversion, vivid imagery and sensational hyperbole, for attaining idealisation, infallibility, fairness and equity. Social consciousness, metaphysical contents and aesthetics in the factions by Hirsi Ali, Thandi Lujabe-Rankoe, Wole Soyinka and Nawal el Saadawi are connected through fictionalized socio-political realities, contextualised within experiential exigencies, and creative lingualiterary resources of the writers. Thus, their convergence is instrumental to projecting the writers‘ perspectives, and the metaphysical and socio-cultural pulses of African societies.